Coexistence of atypical hemolytic uremic syndrome and crescentic IgA nephropathy treated with eculizumab: a case report - Matsumura, Daisuke (Clin Nephrol Case Stud, 2016)
Rapid progression to end-stage renal disease has been reported in a minority of patients with immunoglobulin A (IgA) nephropathy. In particular, crescentic IgA nephropathy has a poor prognosis in patients with a higher initial serum creatinine level. The complement system plays an important role in the pathogenesis of crescentic IgA nephropathy. Atypical hemolytic uremic syndrome (aHUS), which is characterized by thrombotic microangiopathy, is distinct from Shigatoxin-induced HUS and thrombotic thrombocytopenic purpura. aHUS is associated with dysregulation of the alternative complement system. Eculizumab, an anti-C5 antibody, is effective in limiting complement activation in patients with paroxysmal nocturnal hemoglobinuria, aHUS, or refractory IgA nephropathy in some case reports. We herein report the case of a 42-year-old man with acute kidney injury (AKI) clinically and histologically diagnosed with the coexistence of aHUS and crescentic IgA nephropathy. The patient was treated with steroids, plasmapheresis, and hemodialysis; however, eculizumab treatment was initiated on hospital day 21 due to resistance to and dependence on the conventional aggressive therapy. Clinical remission of aHUS was achieved on day 70, but the renal function failed to recover from dialysis dependence. To the best of our knowledge, this is the first report showing the clinical course of a refractory patient with the coexistence of aHUS and crescentic IgA nephropathy treated with eculizumab. This case highlights the clinical importance of early diagnosis and appropriate initiation of eculizumab for the treatment of this type of AKI.